The Impacts of Implementing Education for International Mindedness on Students’ Global Mindset in Dubai’s American Curriculum Schools - GAMAL EL DIN, AZZA MAHMOUD (2021)
In the current age of globalization, schools are required to develop global leaders who are internationally minded to live, work and compete at an international level. International mindedness has three main pillars: multilingualism, intercultural understanding and global engagement. International schools can set a model of educating students towards international mindedness by enhancing their knowledge of other world cultures and engaging them in global environmental issues. The study was supported by Vygotsky’s social constructivist theory, Wilber’s integral theory and Mezirow’s transformative learning theory. The main purpose of the study was to investigate the impact of implementing education for international mindedness on students’ global mindset in Dubai’s American curriculum schools. Three international accredited schools were targeted for the research. Sequential mixed methods design has been utilised in this study in three stages. Document analysis of the participating schools’ vision, mission statement, core values as well as lesson plans were conducted in the first stage of the study. In the second stage, the study explored school leaders and teachers’ perceptions of international mindedness through the Global Mindedness Scale (GMS), which was distributed to 100 school leaders and teachers. Furthermore, students’ awareness of globalization and global citizenship questionnaire was distributed to 682 high school students. The final stage of the study was the semi-structured interviews, which were conducted with 10 school leaders and 11 teachers and 3 focus groups, consisting of around 6 to 8 students in each group from grades 9 to 12. The findings revealed that school leaders and teachers demonstrated high perceptions of international mindedness with no significant differences between the three schools. Results also highlighted a significant relationship between school leaders and teachers’ international mindedness and students’ global mindset. Based on Wilber’s integral theory, students’ experience of international mindedness can be identified by the development of intercultural identity, the ability to take alternative perceptions starting from students’ direct environment presented in the school, to the local and then the global level. The study identified several school practices and initiatives that helped in promoting students’ intercultural understanding and global engagement. As for multilingualism, it has been developed through the different clubs at school and the languages taught at the three schools. Based on the findings, the study provides a set of recommendations for school leaders and teachers as well as a roadmap for developing international mindedness and students’ global mindset.